Strategic Policy Planning dor Food Availability in Denpasar City - Miki, Ni Wayan (Journal of A Sustainable Global South; Vol 9 No 1 (2025): February 2025, 2025)
Fisheries and Food Development programs or activities are in accordance with the 5-year strategic planning outlined in the annual performance plan. The development of fisheries and food security Denpasar City supports 7 (seven) programs with 14 (fourteen) activities and 31 (thirty one) sub-activities. There are 2 (two) programs, 3 (three) activities and 7 (seven) sub-activities that are directly related to Policy Strategic Planning for Food Availability in Denpasar City. All programs, activities and sub-activities that are directly related to Policy Strategic Planning for Food Availability in  Denpasar City which have referred to the Ministry of Internal Affairs Number 050-3708 of 2020 which has been outlined in the RPJMD Universal Plan of Denpasar City 2021-2026 in accordance with Denpasar City Regional Regulation Number 5 2021 and the Department of Fisheries and Food Security Strategic Plan for 2021-2026. This Policy Paper was prepared based on primary data collection methods and secondary data collection. Primary data collection is carried out by taking direct data through interviews and other data sources. Secondary data collection was carried out by quoting from other data sources, for example data on food providers in Denpasar City or through literature study. Data processing uses descriptive statistical and qualitative descriptive methods. Descriptive statistics describe data descriptions in the form of numbers, while qualitative descriptive statistics are narratives that explain or support data in the form of numbers. Index Terms — Renja, Food availability .